The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1038/s41598-022-14958-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based evaluation of two insect trapping grids for delimitation surveys

Abstract: In the United States of America, delimitation trapping surveys with square grids have been used for decades for exotic insects without rigorous evaluation. We used simulations to investigate the effectiveness of two representative designs: an 8-km grid for Acrolepiopsis assectella (leek moth) and a 14.5-km grid for Ceratitis capitata (Mediterranean fruit fly, “Medfly”). We investigated grid compositions and design factors, measuring performance as the mean probability of pest capture over all traps, p(capture)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We recently investigated factors affecting the performance of delimitation trapping surveys targeting localized populations for which the published designs have almost always been square grids (CDFA 2013, FAO/IAEA 2018). We found that grid shape and trap attractiveness were important factors affecting detection performance (Caton et al 2021b, Fang et al 2022) and also that many published grids were most likely oversized (Caton et al 2021a).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We recently investigated factors affecting the performance of delimitation trapping surveys targeting localized populations for which the published designs have almost always been square grids (CDFA 2013, FAO/IAEA 2018). We found that grid shape and trap attractiveness were important factors affecting detection performance (Caton et al 2021b, Fang et al 2022) and also that many published grids were most likely oversized (Caton et al 2021a).…”
Section: Introductionmentioning
confidence: 69%
“…Survey diameters could be increased as warranted with no impact on trap numbers, whereas increasing the size of a regular grid means adding new rows of traps. Trap densities are ideally chosen to ensure acceptable P (Detection) [maximization is probably not efficient, see Fang et al (2022)]. In trap-sects, marginal cost increases from using greater densities would only come from additional supply costs and individual trap servicing times, which are probably a small proportion of the total cost.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, simulation models such as “TrapGrid” ( Manoukis et al 2014 ) can extrapolate from the decline in trap captures with distance (e.g., Manoukis et al 2015 , Manoukis and Gayle 2016 ) to estimate the temporal cumulative probability of detecting fruit fly populations in trapping grids with particular configurations ( Fig. 4b ; Fang et al 2022 ).…”
Section: Relative Trapping Effortmentioning
confidence: 99%